Assessment of water samples with complex compositions using microalgal bioassay based on the community level physiological profiling (CLPP). (15th October 2018) - Kim, Jun-Woo; Ray, Madhumita B.; Rehmann, Lars
Abstract: The ability to effectively characterize the response of microalgal communities to changes in water quality is limited. Earlier, a microalgal bioassay was developed based on community level physiological profiling (CLPP). The efficacy of this assay was evaluated using three wetland water samples, a surface water sample, and two wastewater samples (i.e. primary and secondary), all collected from southwestern Ontario, Canada. In addition, the assay was applied to untreated and activated carbon treated oil sand process water (OSPW). YT (Yeast Identification Test Panel) and Biolog plates were successfully utilized for defined microalgal community under both heterotrophic and mixotrophic growth conditions to characterize the changes in the defined microalgal community due to the changes in water type. It was found that, although the degrees of changes in the algal community varied, all tested water samples were distinguished under both growth regimes using principal component analysis (PCA). The variations in the algal community were caused by the differences of the water samples. The response of the assay due to changes in the algal community caused by different waters was found to be very sensitive and could be used to differentiate different water bodies. It further can be used to monitor temporal changes of water quality of the same water body. Highlights: Microalgal assay based on CLPP was used to assess various environmental water samples. The assay was performed under heterotrophic and mixotrophic growth conditions. Distinct growth patterns for water samples were resulted under both growth regimes. Variations in growth patterns were distinguished using PCA. The assay successfully differentiated water bodies with complex compositions.